2019
DOI: 10.1155/2019/7931654
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Metamorphopsia, Visual Acuity, and Central Macular Thickness after Epiretinal Membrane Surgery in Four Preoperative Stages Classified with OCT B-Scan Images

Abstract: Purpose. To observe the changes in metamorphopsia, visual acuity, and central macular thickness (CMT) in patients undergoing vitrectomy for idiopathic epiretinal membranes (iERM); all of which were preoperatively stratified into 4 stages according to the anatomical structure of the macula seen on the optical coherence tomography (OCT) b-scan images. Methods. A total of 108 eyes of 106 patients were included. We evaluated and classified the severity of each preoperative ERM based on OCT. Changes in the best-cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…In Groups 1–3, a consistent stage-by-stage course of OCT-morphological macular changes in progression of ERM was presented, which was also described in publications by Fung et al [ 6 ] and Mao et al [ 21 ]. In Groups 4 and 5, a complementary tractive component is pathophysiologically mandatory.…”
Section: Methodssupporting
confidence: 78%
See 1 more Smart Citation
“…In Groups 1–3, a consistent stage-by-stage course of OCT-morphological macular changes in progression of ERM was presented, which was also described in publications by Fung et al [ 6 ] and Mao et al [ 21 ]. In Groups 4 and 5, a complementary tractive component is pathophysiologically mandatory.…”
Section: Methodssupporting
confidence: 78%
“…Group 1: Completely or partially preserved foveolar depression Group 2: Isolated elevation of the foveola Group 3: Elevation of the foveola with an ectopy of INL and/or IPL (EIFL) Group 4: MLH of tractive genesis Group 5: VMT In Groups 1-3, a consistent stage-by-stage course of OCT-morphological macular changes in progression of ERM was presented, which was also described in publications by Fung et al [6] and Mao et al [21]. In Groups 4 and 5, a complementary tractive component is pathophysiologically mandatory.…”
Section: Methodssupporting
confidence: 63%
“…Anteroposterior forces cause the macula to thicken; thickening of the macula and loss of foveal depression are easily visualized with OCT. In our previous study (Mao et al 2019), we applied the classification method developed by Govetto and colleagues to the study of metamorphopsia caused by iERM. We found that the postoperative BCVA and central macular thickness (CMT) were significantly improved at all stages; however, the metamorphopsia of stage 2 and stage 3 iERM was improved after surgery, while that of stage 4 iERM was not.…”
Section: Discussionmentioning
confidence: 99%
“…At early stages of iERM there are commonly no symptoms, whereas in advanced cases of the disease, patients may complain of visual impairment, distortion, macropsia, or monocular diplopia affecting their quality of life. 4,5…”
Section: Introductionmentioning
confidence: 99%